THE EFFECT OF QUALITY OF WORK LIFE AND INTERNAL CORPORATE SOCIAL RESPONSIBILITY ON EMPLOYEE ENGAGEMENT AND ITS IMPLICATIONS ON HOSPITAL EMPLOYEE PERFORMANCE (Survey Study at Hawari Essa Hospital, Tegal Regency) - Ranita Rizky Putri; Sri Rochani; Rukhiyat Syahidin; Vip Paramarta; Farida Yuliaty; Etty Sofia (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study to determine the influence of quality of work life (QWL) and internal corporate social responsibility (ICSR) on employee engagement that's implications on employee performance at Hawari Essa Hospital, Tegal. The results of the path coefficient test show about the significance value of the influence of QWL on employee engagement is 0.000, the significance value of the influence of ICSR on employee engagement is 0.008, the significance value of the influence of employee engagement on performance is 0.000, the significance value of the influence of ICSR on performance is 0.017. The results of the Blindfolding test of the Q-Square value of the employee engagement variable are 0.536. The significance value of the indirect effect test the influence of QWL on performance through employee engagement is 0.000, the significance value of the influence of ICSR on performance through employee engagement is 0.021. The findings are that QWL has a positive effect on employee engagement of Hospital employees, ICSR has a positive effect on employee engagement of Hospital employees, QWL and ICSR simultaneously have an effect on employee engagement of Hospital employees, employee engagement has a positive effect on employee performance of Hospital employees, QWL has a positive effect on employee performance of Hospital employees, ICSR has a positive effect on employee performance of Hospital employees, QWL has an effect on employee performance of Hospital employees through employee engagement and ICSR has an effect on employee performance of Hawari Essa Hospital through employee engagement.